Effect of mass media and Internet on sexual behavior of undergraduates in Osogbo metropolis, Southwestern Nigeria - Asekun-Olarinmoye OS; Asekun-Olarinmoye EO; Adebimpe WO; Omisore AG (Dove Medical Press, 2014)
Olusesan S Asekun-Olarinmoye,1 Esther O Asekun-Olarinmoye,2 Wasiu O Adebimpe,2 Akin G Omisore21Department of Mass Communication, Babcock Business School, Babcock University, Ilisan-Remo, Ogun State, Nigeria; 2Department of Community Medicine, Faculty of Clinical Sciences, College of Health Sciences, Osun State University, Osogbo, Osun State, NigeriaIntroduction: The influence of media portrayals of sexual attitudes and normative expectations of young people at a critical developmental stage is of public health concern.Objectives: To examine the role of mass media and Internet utilization in shaping the sexual health attitudes and behaviors of young undergraduates in Osogbo metropolis, Osun State, Nigeria.Materials and methods: In a descriptive cross-sectional study, 400 undergraduates were selected using a multistage random sampling technique. Four hundred and fifty pretested, semistructured questionnaires were distributed; of these, 400 were returned properly filled. Data were analyzed using SPSS statistical software version 16.Results: Mean age of respondents ± standard deviation was 23.6±2.99 years. Most were aware of the various forms of mass media (>95%). Most (64.0%) respondents spent 1–5 hours watching television, daily, and most used the Internet often. About 38.3% and 24.2% of respondents used the Internet and radio/television, respectively, as sources of information on sexual issues. Most respondents used the Internet for school assignments (83.0%, n=332), electronic mail (89.0%, n=356), and for accessing sexually explicit materials (74.5%, n=298). Most of the respondents (73.5%) opined that the Internet has a bad influence on youths' sexual behavior, although accessing the Internet for sexual material or movies was acceptable to 25.3% of them. Of the 226 respondents who had ever had sex, 226 (100%), 37 (16.4%), 31 (13.7%), and 10 (4.4%) practiced coitus, oral sex, masturbation, and anal sex, respectively; 122 (54.0%) always used condoms, whereas 90 (40.0%) never used condoms during sexual activity; 33 (14.6%) had had sex with commercial sex workers. Further analysis showed that those who were yet to marry (single) were less likely to be sexually experienced than those who were married (adjusted odds ratio [AOR] =0.075, 95% confidence interval [CI] =0.008–0.679), and those who said accessing the Internet for sexual material is not acceptable to them were also less likely to be sexually experienced than those to whom it was acceptable (AOR =0.043, 95% CI =0.016–0.122). Predictors of having multiple sexual partners include the sex of the respondent and the frequency of Internet use, with females (AOR =0.308, 95% CI =0.113–0.843) and those who rarely use the Internet less likely to have multiple sexual partners.Conclusion: We conclude that uncontrolled exposure to mass media and Internet could negatively influence the sexual patterns and behavior of youths.Keywords: mass media, Internet, sexual behavior, undergraduates